Exploring the Value Evaluation of Natural Resource Assets on Uninhabited Islands - ZHANG Wenzhu; WU Bin; CHEN Zhehua (Haiyang Kaifa yu guanli)
As an important component of the national territory, uninhabited islands are of great significance for the sustainable development of China's national economy and society. The valuation of natural resource assets is crucial for scientific management and rational utilization of uninhabited islands. The paper takes uninhabited islands as the research object, and based on the concept of natural resource assets, divides the value of natural resource assets in uninhabited islands into private goods attribute value (economic value) and public goods attribute value (social ecological value). Based on the characteristics of two types of values, this paper analyzes the monetization path of the economic and social ecological values of uninhabited islands, clarifies the idea of unifying the ecological capital and economic capital of uninhabited islands, summarizes the evaluation methods of various types of uninhabited island values, and provides reference and reference for establishing the evaluation method system of natural resource assets in uninhabited islands.